Oral-Facial-Digital Syndrome Type 1: Oral Findings in a 6-Year-Old Girl - Kırzıoglu, Zuhal; Oz, Esra (Journal of Pediatric Genetics, 2018)
Oral-facial-digital syndrome (OFDS) is a group of congenital anomalies with 13 different forms. OFDS type 1 (OFDS1) is a developmental genetic anomaly related to the X chromosome, that is often seen in girls, and affects the face, oral cavity, and extremities. In this study, we discuss the oral findings of a 6-year-old girl with OFDS1 and her situation after 2.5 years.
Keywords: genetics; oral findings; oral-facial-digital syndrome type 1